Analisis Isi Ulasan Google Maps Terkait Aspek Perpustakaan di Perpustakaan Jakarta Cikini - Nabila Nurazizah; Lili Sudria Wenny (Universitas Islam Negeri Imam Bonjol Padang, 2025)
Users in the digital age tend to seek information through online platforms and Google maps is one such platform that allows users to assess anything including public libraries. This research aims to find out what aspects of the library are most dominantly discussed in Jakarta Cikini Library after revitalization. This research uses quantitative content analysis with a descriptive approach. Technique sampling used was purposive sampling by limiting the review data after the revitalization of the library which was calculated from July 2022 to March 2024 as many as 1186 reviews and selecting reviews that include text as many as 667 reviews. From 667 reviews that included the text, a separation per sentence to make it easier to analyze the sub-category aspects, resulting in 1524 review sentences and processed with proportional units and positive, negative and neutral value. The concept used in this research is the ideal library by Sutarno NS with five aspects of the library namely building, collection, equipment and furniture, labor, and services. The analysis found that the building category became the most discussed category by the users with the sub-category of convenience has dominant positive value means that the users consider the library building is comfortable enough in fulfilling wants and needs in conducting library activities.